Komunikasi Pemberdayaan Masyarakat Desa Pematang Johar dalam Pengelolaan Sampah Plastik Berbasis Ecobrick - Arifin Saleh; Mujahiddin Mujahiddin; Sigit Hardiyanto (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2023)
The Central Statistics Agency (BPS) released data on plastic waste in Indonesia that has reached 66 million tonnes per year. In the village of Pematang Johar, to be precise, in Hamlet 15, the Suka Mulia Garbage Bank has been established, which currently has 60 customers. In this waste bank, residents are starting to actively save and manage plastic waste using an ecobrick approach. This study aims to describe and analyze community empowerment communication in Pematang Johar Village in Ecobrick-Based Plastic Waste Management. This research design is qualitative with a descriptive approach. The data in this study consisted of secondary data and primary data, both of which were analyzed using an interactive model as proposed by Miles and Huberman, which consisted of three main things: data reduction, data presentation, and conclusion/verification. The results of this study found a form of community empowerment communication in ecobrick-based waste management in Pematang Johar Village starting from the dissemination of ecobrick ideas to students reciting the Koran by inviting these students to collect waste from homes and the village environment and teach the practice of making ecobrick every Saturday night. In addition, a form of empowerment communication is also carried out by holding student art performances decorated with ecobrick handicraft.